37.0k views
2 votes
4x-9y=9

-x+3y=6
Consider the system of linear equations below.

Rewrite one of the two equations above in the form ax + by = c, where a, b, and c are constants, so that the sum of the new equation and the unchanged equation from the original system results in an equation in one variable.

ax+by=c

2 Answers

4 votes

Answer:

Second equation:

-x + 3y = 6

Multiply the second equation by 4 on both sides:

-4x + 12y = 26

Explanation:

User Wit
by
5.5k points
3 votes

Answer:

-4x + 12y = 24

Explanation:

4x - 9y = 9

-x + 3y = 6

To eliminate x, we need 4x in the second equation.

Multiply both sides of the second equation by 4.

-4x + 12y = 24

User Carlos Afonso
by
5.6k points